1994
DOI: 10.1111/j.1471-0528.1994.tb13579.x
|View full text |Cite
|
Sign up to set email alerts
|

The quality of routinely collected maternity data

Abstract: Objective To assess the validity of clinical information held on a regional maternity database, the St Mary's Maternity Information System (SMMIS). Design A retrospective review of 892 maternity case notes and matched SMMIS records, by a midwife trained in clinical coding techniques. Setting Three maternity units in the North West Thames Region. Main outcome measures Percentage agreement for 17 directly recorded SMMIS data items and equivalent data abstracted from the notes. Frequencies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
1
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 11 publications
(8 reference statements)
1
51
1
1
Order By: Relevance
“…Studies have concluded that the completeness and quality of the information recorded within SMMIS is good. For example, studies comparing the information recorded on the computerised database against case notes found a very high degree of corroboration, and a high level of consistency across different hospitals (15,16). 6 The SMMIS database is extremely useful for the study of pregnancy outcomes by place of birth, because it overcomes many of the problems inherent within other UK data sources.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have concluded that the completeness and quality of the information recorded within SMMIS is good. For example, studies comparing the information recorded on the computerised database against case notes found a very high degree of corroboration, and a high level of consistency across different hospitals (15,16). 6 The SMMIS database is extremely useful for the study of pregnancy outcomes by place of birth, because it overcomes many of the problems inherent within other UK data sources.…”
Section: Methodsmentioning
confidence: 99%
“…The database has been previously validated for commonly recorded variables including intrauterine death. 13 BMI was calculated as weight at antenatal booking (kg), divided by height (m) squared. The subjects were divided into groups according to maternal BMI at booking using body mass groupings recommended by Abrams and Parker 14 (normal, BMI 20 -< 25; moderately obese, BMI 25 -< 30, and very obese, BMI > 30).…”
Section: Methodsmentioning
confidence: 99%
“…The aim of this study was to examine pregnancy outcome in obese women compared to those of normal weight by reviewing a large number of singleton pregnancies using a validated database. 13 We aimed to test the hypothesis that obesity, as determined by maternal body mass index (BMI), is associated with adverse outcomes for mother and baby, and to quantify this risk after allowing for possible confounding factors.…”
Section: Introductionmentioning
confidence: 99%
“…Research performed by obtaining data from SMMIS 10 has been criticised in the past 11,12 on the grounds that such a database may be insufficiently accurate to support research. Cleary et al 13 addressed this issue by retrospectively comparing 892 maternity casenotes and matched SMMIS records and found that out of 17 data items compared there was 95% agreement or better for 10 items and all except two exceeded 80%. By performing a validation exercise in the current study we would not only strengthen the conclusions of the study, but also add to the literature on the validation of computerised maternity information systems.…”
Section: Bjog: An International Journal Of Obstetrics and Gynaecologymentioning
confidence: 99%